2008
DOI: 10.1002/hed.20937
|View full text |Cite
|
Sign up to set email alerts
|

First‐year quality of life assessment of an intra‐arterial (RADPLAT) versus intravenous chemoradiation phase III trial

Abstract: Background. We report the results of a multicenter randomized phase III study, assessing quality of life (QOL) in intra-arterial (IA) versus standard intravenous (IV) chemoradiation in advanced head and neck cancer.Methods. Two hundred seven patients with inoperable stage IV disease-152 men and 55 women; mean age, 55 yearswere included in this study. The patients were treated with standard radiotherapy with 4 weekly IA or 3 weekly IV cisplatin infusions. The QOL assessments carried out were EORTC-C30, H&N35, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 21 publications
6
77
1
3
Order By: Relevance
“…Encouraging functional outcomes were observed, with a 3% gastrostomy tube dependence rate (in a single living patient) and 8% aspiration rate, comparing favorably with existing literature, with reported rates of 15% to 30% [22][23][24] and up to 69%, 25,26 respectively. The basis for these favorable functional outcomes is unclear, and further studies are needed to determine the effects of sequential therapy, newer radiotherapy techniques, and use of a riskbased local therapy model on swallowing abilities.…”
Section: Discussionsupporting
confidence: 72%
“…Encouraging functional outcomes were observed, with a 3% gastrostomy tube dependence rate (in a single living patient) and 8% aspiration rate, comparing favorably with existing literature, with reported rates of 15% to 30% [22][23][24] and up to 69%, 25,26 respectively. The basis for these favorable functional outcomes is unclear, and further studies are needed to determine the effects of sequential therapy, newer radiotherapy techniques, and use of a riskbased local therapy model on swallowing abilities.…”
Section: Discussionsupporting
confidence: 72%
“…These results are similar to those previously reported where the majority of patients resumed soft diets, although reported ongoing diet restrictions at 12 months post-treatment [12,[15][16][17]. A number of reports describe "swallowing solids" [31] or "more or less normal oral feeding" [32] as positive outcomes for the CRT population without quantifying their function in more detail. Less information is known about the AFRT population diet tolerance post-treatment with initial data suggesting mild difficulty swallowing solids post-treatment [6].…”
Section: Resultssupporting
confidence: 88%
“…15 We noticed an increase in nausea and vomiting in our study during treatment and post completion of treatment which gradually decreased over a period of 1month and still further 3months post completion of treatment but not reaching to pre-treatment levels. Ackerstaff et al 16 evaluated the quality of life of 207 patients with inoperable stage IV head and neck patients undergoing concurrent chemo-radiation and found that there was significant increase in nausea and vomiting on 7 th week assessment with IV cisplatin based chemotherapy which improved over a 3-month period post completion of treatment and almost reaching baseline at 12-months post therapy. 16 Pain was a major problem for patients in our study during treatment and on completion of treatment with major pain relief seen after 1 month, reaching baseline levels post 3 months of treatment.…”
mentioning
confidence: 99%
“…Ackerstaff et al 16 evaluated the quality of life of 207 patients with inoperable stage IV head and neck patients undergoing concurrent chemo-radiation and found that there was significant increase in nausea and vomiting on 7 th week assessment with IV cisplatin based chemotherapy which improved over a 3-month period post completion of treatment and almost reaching baseline at 12-months post therapy. 16 Pain was a major problem for patients in our study during treatment and on completion of treatment with major pain relief seen after 1 month, reaching baseline levels post 3 months of treatment. Pain in our study was mainly caused by mucositis.…”
mentioning
confidence: 99%
See 1 more Smart Citation